Sistema web-multimedia con asistentes de ayuda para estimulación de lenguaje y agilidad mental de niños de 3 a 5 años en el Centro Infantil El Roble - Chasiquiza Rivera, María José (2023)
This work focuses on improving the motivation of children aged 3 to 5 years, and recognizes the need to change the university curriculum. In an increasingly technological world, it is important to consider the potential that technology offers today to ensure the professional development of children in the future. Innovations in education are proven to be a fundamental part of learning and retaining information from an early age. Designed to stimulate children's cognitive development, the learning system is based on learning principles using tools that promote learning through play. These games not only capture children's attention, but are also effective in ensuring that they match their level of development and understanding. Thus, technology becomes an influential partner in the learning process, providing an interactive and engaging program that promotes fun learning. This work focuses on improving the motivation of children aged 3 to 5 years, and recognizes the need to change the university curriculum. In an increasingly technological world, it is important to consider the potential that technology offers today to ensure the professional development of children in the future. Innovations in education are proven to be a fundamental part of learning and retaining information from an early age. Designed to stimulate children's cognitive development, the learning system is based on learning principles using tools that promote learning through play. These games not only capture children's attention, but are also effective in ensuring that they match their level of development and understanding. Thus, technology becomes an influential partner in the learning process, providing an interactive and engaging program that promotes fun learning.